The Role of Chemerin in Upper Gastrointestinal Cancer - Adam Mylonakis; Maximos Frountzas; Irene Lidoriki; Alexandros Kozadinos; Areti Kalfoutzou; Eva Karanikki; Iliana Tsikrikou; Maria Kyriakidou; Dimitrios Theodorou; Konstantinos G. Toutouzas; Dimitrios Schizas (Metabolites)
Background/Objectives: Chemerin, which is a multifunctional cytokine and adipokine, has been implicated in inflammatory and metabolic processes and might play a role in upper gastrointestinal (GI) malignancies, particularly gastric and esophageal cancer. The aim of this review is to explore the role of chemerin in the pathophysiology of upper GI cancers, as well as its potential as a biomarker for early detection and as a therapeutic target. Methods: A comprehensive review of recent studies about chemerin’s biochemical properties and interaction with its receptors, as well as its effects on inflammatory responses, immune regulation, and metabolic processes, was conducted. The clinical implications of chemerin for gastric and esophageal cancer were analyzed, whereas the potential therapeutic strategies targeting chemerin were discussed. Results: Elevated chemerin levels are associated with poor prognosis in gastric cancer and promote invasiveness and metastasis in esophageal cancer. Chemerin receptor antagonists show promising results in inhibiting cancer cell migration, invasion, and progression. Conclusions: Chemerin could represent a valuable prognostic biomarker and therapeutic target for upper GI cancers. Future observational studies should validate its clinical applications and investigate the efficacy of chemerin inhibitors as potential therapeutic targets.